2017
DOI: 10.1002/14651858.cd000081.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Selective versus routine use of episiotomy for vaginal birth

Abstract: Background Some clinicians believe that routine episiotomy, a surgical cut of the vagina and perineum, will prevent serious tears during childbirth. On the other hand, an episiotomy guarantees perineal trauma and sutures. Objectives To assess the effects on mother and baby of a policy of selective episiotomy ('only if needed') compared with a policy of routine episiotomy ('part of routine management') for vaginal births. Search methods We sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
374
5
70

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(460 citation statements)
references
References 52 publications
(251 reference statements)
11
374
5
70
Order By: Relevance
“…These results were consistent with those of the Euro-peristat project, which described an increase in the rate of severe perineal tears for all vaginal deliveries between 2004 and 2010 in all European countries, except Germany and Norway [28]. This issue is still the subject of a controversial debate [7, 9, 20, 2932]. Randomized trials showed no increase in severe perineal tears related to the restrictive use of episiotomy [3].…”
Section: Discussionsupporting
confidence: 87%
“…These results were consistent with those of the Euro-peristat project, which described an increase in the rate of severe perineal tears for all vaginal deliveries between 2004 and 2010 in all European countries, except Germany and Norway [28]. This issue is still the subject of a controversial debate [7, 9, 20, 2932]. Randomized trials showed no increase in severe perineal tears related to the restrictive use of episiotomy [3].…”
Section: Discussionsupporting
confidence: 87%
“…The recommended use is restrictive (only in the case of indications such as foetal distress and the urgent need to finish the labour quickly) (Jiang et al, 2017). In case of the need for episiotomy, the correct timing to perform the procedure is when 3-4 cm of presenting part of the baby is visible in between the contractions.…”
Section: Episiotomymentioning
confidence: 99%
“…Episiotomy also weakens perineal muscles (Walsh, 2007) and can predispose woman to perineal trauma, therefore routines use is not advised (Jiang et al, 2017).…”
Section: Episiotomymentioning
confidence: 99%
“…Episiotomy The recommended use is restrictive (only in the case of indications such as foetal distress and the urgent need to finish the labour quickly) (Jiang et al, 2017). In case of the need for episiotomy, the correct timing to perform the procedure is when 3-4 cm of presenting part of the baby is visible in between the contractions.…”
Section: Referencesmentioning
confidence: 99%